Development of Ethnomathematics-based Hybrid Learning Model Using a Cybergogy Approach to Improve Mathematical Proficiency of Prospective Elementary School Teachers - Muhammad Fendrik; Zariul Antosa; Gustimal Witri; Rahmat Rizal Andhi (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThis study aims to develop a hybrid learning model based on ethnomathematics with a cybergogy approach to improve mathematical proficiency of prospective elementary school teachers. This study is an R & D (Research and Development) study using the Plomp model (preliminary research stage, development or prototyping stage, and assessment stage). In data collection, researchers used questionnaires, observations, and tests. Based on the validation results by learning design experts, material experts, and practitioners, the learning model developed meets the criteria of being very feasible. Based on the results of observations of the implementation of lectures, both lecturer and student activities and lecturer and student responses, the learning model developed meets the criteria of being practical. And based on the results of limited trials and expanded trials, it shows that there is a significant difference in the average score of mathematical proficiency of prospective elementary school teachers between those who receive learning with a hybrid learning model based on ethnomathematics ( = 84) with the average score of mathematical proficiency of prospective elementary school teachers who receive expository learning ( = 75). So, it can be concluded that the hybrid learning model based on ethnomathematics with a cybergogy approach meets the criteria of being feasible, practical, and effective. The implications of the research results indicate that the application of a hybrid learning model based on ethnomathematics with a cybergogy approach can have a positive impact on improving the mathematical proficiency of prospective elementary school teachers in mathematics learning.Keywords: hybrid learning model, ethnomathematics, cybergogy approach. AbstrakPenelitian ini bertujuan untuk mengembangkan model pembelajaran hybrid berbasis etnomatematika dengan pendekatan cybergogy untuk meningkatkan kecakapan matematika calon guru sekolah dasar. Penelitian ini merupakan penelitian R & D (Research and Development) dengan menggunakan model Plomp (tahap penelitian pendahuluan, tahap pengembangan atau prototyping, dan tahap asesmen). Dalam pengumpulan data, peneliti menggunakan angket, observasi, dan tes. Berdasarkan hasil validasi oleh ahli desain pembelajaran, ahli materi, dan praktisi, model pembelajaran yang dikembangkan memenuhi kriteria sangat layak. Berdasarkan hasil observasi pelaksanaan perkuliahan, baik aktivitas dosen maupun mahasiswa serta respon dosen dan mahasiswa, model pembelajaran yang dikembangkan memenuhi kriteria praktis. Dan berdasarkan hasil uji coba terbatas dan uji coba diperluas menunjukkan bahwa terdapat perbedaan yang signifikan skor rata-rata kecakapan matematika calon guru sekolah dasar antara yang mendapatkan pembelajaran dengan model pembelajaran hybrid berbasis etnomatematika ( = 84) dengan skor rata-rata kecakapan matematika calon guru sekolah dasar yang mendapatkan pembelajaran ekspositori ( = 75). Sehingga dapat disimpulkan bahwa model pembelajaran hybrid berbasis etnomatematika dengan pendekatan cybergogy memenuhi kriteria layak, praktis, dan efektif. Implikasi hasil penelitian menunjukkan bahwa penerapan model pembelajaran hybrid berbasis etnomatematika dengan pendekatan cybergogy dapat memberikan dampak positif terhadap peningkatan kecakapan matematika calon guru sekolah dasar dalam pembelajaran matematika.Kata kunci: model pembelajaran hybrid, etnomatematika, pendekatan cybergogy.